Clinical gestational age assessment in newborns using the new Ballard score - Erman Erman; Wayan Retayasa; Soetjiningsih Soetjiningsih (Indonesian Pediatric Society, 2006)
Background The new Ballard score (NBS) is presently consid-ered to be the most reliable method for estimating clinical gesta-tional age (GA) in newborn infants.Objective The aim of this study was to compare the NBS andDubowitz/Finnstrom score against ultrasonography assessment ofgestational age.Methods A cross sectional randomized study involving neonatesborn in Sanglah Hospital, Bali, June to August 2004 was carriedout. Gestational age was estimated within the first 24 hour by ei-ther Dubowitz/Finnstrom score or NBS confirmed by USG (C-GLMP) as the gold standard.Results One hundred and fifty-five newborns were enrolled in thisstudy. Subjects were randomly divided into two groups, theDubowitz/Finnstrom score group (76 newborns) and NBS group(79 newborns). The mean age of mothers was 28.4 years old; meanbirth weight was 3151.3 g (SD 596.3 g). The proportion of small forGA, appropriate for GA, and large for GA were 6%, 77% and 17%,respectively. Pearson correlation ( r ) between C-GLMP andDubowitz/Finnstrom score was 0.71 (P<0.005); and with NBS was0.79 (P<0.005) .Conclusion The strength of correlation between either NBS orDubowitz/Finnstrom score and USG assessment of gestational ageare similar